ALPINE-APENNINE OPHIOLITIC PERIDOTITES: NEW CONCEPTS ON THEIR COMPOSITION AND EVOLUTION - Piccardo, Giovanni B.; Müntener, Othmar; Zanetti, Alberto (Ofioliti, 2004)
Ophiolites exposed in the Alpine-Apennine mountain range represent the oceanic lithosphere of the Ligurian Tethys, a small oceanic basin separating the Europe and Adria plates in Mesozoic times. Most of the peridotites represent former subcontinental mantle which was: (i) isolated from the convective mantle at different times (from Proterozoic to Permian); (ii) accreted to the thermal lithosphere, where it cooled along a conductive geothermal gradient under spinel peridotite facies conditions. Our investigations reveal important records of melt/peridotite interaction and melt impregnation (i.e. formation of plagioclase peridotites), which were related to asthenosphere/lithosphere interaction occurred during lithospheric extension leading to rifting and drifting of the Jurassic Ligurian Tethys. The early asthenosphere/ lithosphere interaction was caused by the reactive percolation of asthenospheric melts, which induced significant depletion, refertilization and heating of the lithospheric mantle peridotites. The plagioclase peridotites of the Alpine-Apennine ophiolites mostly derive from melt impregnation, whereas part of the depleted spinel peridotites result from reactive percolation of depleted MORB-type melts, rather than being solely refractory residua after nearfractional melting. The presence of large areas of impregnated peridotites indicates that significant volumes of melts were trapped in the lithospheric mantle. Subsequently, the asthenospheric melts reached the surface, both intruding as MORB gabbroic bodies or extruding as MORB lava flows. These peridotites record two magmatic cycles: (1) An early magmatic, non-volcanic stage: the early diffuse porous flow percolation and impregnation by single melt increments, focused percolation in dunite channels and intrusion of MORB-type melts; (2) A late magmatic, volcanic stage: the late intrusion and extrusion of magmas deriving from aggregated MORB liquids. The sequence of periods characterized by absence (non-volcanic or a-magmatic or magma-starved stages) and presence (volcanic or magmatic stages) of volcanism represents one of the most peculiar feature of slow and very-slow spreading ridges. Melt stagnation in the oceanic lithospheric mantle has been proposed as the dominant mechanism of peridotite impregnation and plagioclase peridotite formation along slow spreading systems. It could be that amagmatic periods of (ultra-) slow spreading ridges are characterized by melt stagnation in the thermal lithosphere, leading to plagioclase peridotite formation. Our results evidence the great variability in terms of melt composition and regime of melt percolation during the rift evolution. They provide, moreover, a mechanism to explain non-volcanic and volcanic stages during the rift evolution of the Ligurian Tethys and might be equally applicable to modern slow spreading ridges, which are characterized by variable magmatic (volcanic) and amagmatic (non-volcanic) stages.